The Efficacy of Amniotic Membrane Stem Cell (AMSC) Metabolite Product and Vitamin E for Wrinkles, Spots, and Pores in Photoaging - Rahmadewi Rahmadewi; Retha Retha; Dyah Ayu Pitasari; Vidyani Adiningtyas Kusumastanto; Agatha Anindita Ayu Ardhaninggar; Irmadita Citrashanty; Maylita Sari; Menul Ayu Umborowati; Cita Rosita Sigit Prakoeswa (Hindawi Limited, 2020)
Background. It is expected that a combination of amniotic membrane stem cell metabolite product (AMSC-MP) and vitamin E after fractional CO2 laser as laser-assisted drug delivery (LADD) will provide better effects in photoaging treatment as the combination reaches the target. This promises an option for photoaging therapy in the future. Materials and Methods. Sixty women with photoaged skins were involved in this experimental study. They were then divided into two groups. The treatment group received a topical combination of AMSC-MP and vitamin E, and the control group received AMSC-MP alone after fractional CO2 laser. The treatment was repeated three times. Result. The Janus assessment results showed a significant difference in pores in the third observation, and the average pore improvements in the treatment group were better than the control group. Wrinkle, UV spot, and polar spot did not show any significant difference. Conclusion. A combination of the amniotic membrane stem cell metabolite product (AMSC-MP) and vitamin E after fractional CO2 laser as LADD only improves pores in photoaged skins.